A survey of the use of the vernacular as medium of instruction in twelve Philippine public schools with particular reference to Iloilo - Jardenil, Neva A. 1928- (Quezon City College of Education, University of the Philippines Diliman, 1962)
This study provides supplementary information on the use of the vernacular as medium of instruction. First part of the paper is a survey of attitudes and problems on the use of vernacular, and the second part is a follow-up of the Iloilo experiment.
Thesis
Keywords: Education, Primary; Languages -- Political aspects; Philippine languages